Medium-term prognosis of survival and hospitalization of patients after permanent pacemaker implantation based on BNP, high-sensitivity troponin T, and left atrium volume index - Kaziród-Wolski, Karol; Sielski, Janusz K.; Grabowska, Urszula (Medical Studies/Studia Medyczne, 2017)
Introduction : Determination of predictors of survival and hospitalization can optimise a medical care of patient with permanent pacemaker. Aim of the research : Use of the B-type natriuretic peptide (BNP), high-sensitivity troponin T (TnT hs), and left atrial volume index (LAVI) to control survival and hospitalizations due to cardiovascular causes in patients after pacemaker implantation. Material and methods : The study covered a sample of 123 patients qualified for pacemaker implantation. During 23-month observation, cyclic BNP, TnT hs and LAVI examinations were performed. Mortality and hospitalization rate in groups with normal and elevated values were assesed using Kaplan-Meier curves. Results : A statistical relationship was observed between survival and increased initial BNP plasma level (log-rank test = 2.11, p < 0.05). Significantly higher frequency of hospitalizations was observed with a higher initial BNP plasma level (log-rank test = 2.01, p < 0.05). No statistically significant relationships were found between the TnT hs concentration and the duration of survival and hospitalizations. A strong tendency was confirmed (p < 0.10) towards a higher probability of the survival of patients with low values of LAVI, compared to patients with high values of LAVI. Conclusions : Results of the study conducted in regional centre (over 1000 implantations per year) confirmed that BNP peptide is an important indicator of survival and hospitalization due to cardiovascular causes after permanent pacemaker implantation. From among the 3 parameters examined: BNP, TnT hs LAVI, only BNP peptide and LAVI may be justified in the evaluation of patients after pacemaker implantation. Determination of BNP for evaluation medium-term prognosis of survival and hospitalization may be considered during routine pacemaker control visit.